Localization of Postsynaptic Density-93 to Dendritic Microtubules and Interaction with Microtubule-Associated Protein 1A - Brenman, Jay E. (J Neurosci, 1998)
Postsynaptic density-93 (PSD-93)/Chapsyn-110 is a member of the membrane-associated guanylate kinase (MAGUK) family of PDZ domain-containing proteins. MAGUKs are widely expressed in the brain and are critical elements of the cytoskeleton and of certain synapses. In the ultrastructural studies that are described here, PSD-93 localizes to both postsynaptic densities and dendritic microtubules of cerebellar Purkinje neurons. The microtubule localization is paralleled by a high-affinity in vivo interaction of PSD-93 via its guanylate kinase (GK) domain with microtubule-associated protein 1A (MAP1A). GK domain truncations that mimic genetically identified mutations of a Drosophila MAGUK,discs-large, disrupt the GK/MAP-1A interaction. Additional biochemical experiments demonstrate that intact MAGUKs do not bind to MAP1A as effectively as do isolated GK domains. This appears to be attributable to an intramolecular inhibition of the GK domain by the PDZs, because GK binding activity of full-length MAGUKs is partially restored by a variety of PDZ ligands, including the C termini of NMDA receptor 2B, adenomatous polyposis coli (APC), and CRIPT. Beyond demonstrating a novel cytoskeletal link for PSD-93, these experiments support a model in which intramolecular interactions between the multiple domains of MAGUKs regulate intermolecular associations and thereby may play a role in the proper targeting and function of MAGUK proteins.